Therapeutic effects of probiotics on symptoms of depression in children and adolescents: a systematic review and meta-analysis - Chia-Min Chen; Shun-Chin Liang; Cheuk-Kwan Sun; Yu-Shian Cheng; Yen-Hsiang Tang; Cheng Liu; Kuo-Chuan Hung (BMC, 2024)
Abstract This meta-analysis aimed at investigating the therapeutic effects of probiotics against the symptoms of depression in children and adolescents as well as to identify the potential confounders. Following PRISMA guidelines, major databases were searched for randomized controlled trials focusing on effects of probiotics against the symptoms of depression in children and adolescents to analyze the effect size (ES) for primary outcomes (i.e., improvement in depressive symptoms) expressed as standardized mean difference (SMD) and odds ratios (ORs) for continuous and categorical variables, respectively, with 95% confidence interval (CI). Meta-analysis of five studies (692 participants, mean age = 7.33 years, treatment duration 8-104 weeks) demonstrated no significant improvement in depressive symptoms in subjects receiving probiotics (SMD = 0.04, 95% CI: -0.33 to 0.41, p = 0.84, five studies, 692 participants). Subgroup analysis also showed no significant improvement associated with probiotic use relative to controls in the subgroup of studies focusing on individuals diagnosed with neurodevelopmental disorders (SMD = -0.11, 95% CI: -0.73 to 0.51, p = 0.72, three studies, 452 participants) and that recruiting the general population (SMD = 0.24, 95% CI: -0.43 to 0.91, p = 0.48, two studies, 240 participants). However, high levels of heterogeneity were found in both our primary results (I2 = 77%, p = 0.001) and subgroup analyses for those with neurodevelopmental disorders (I2 = 84%, p = 0.002) and the general population (I2 = 79%, p = 0.03). The results did not support the use of probiotics for relieving depressive symptoms compared with controls in children and adolescents diagnosed with neurodevelopmental disorders or in the general population. Nevertheless, given the high level of heterogeneity across the included trials and a lack of studies focusing on those with diagnoses of anxiety or depression in the current meta-analysis, further large-scale clinical investigations are required to elucidate the therapeutic potential of probiotics against depressive symptoms in these populations, especially in those diagnosed with neurodevelopmental disorders or depression.